Eksplorasi Inovatif: Pendekatan dan Teori Terkini dalam Dunia Pendidikan - Lailiyah, Mukhibatul; Maunah, Binti (Allimna: Jurnal Pendidikan Profesi Guru, 2023)
Indicators of a nation's progress can be seen from the level of education achieved. Education has an important role in developing individuals into human beings who have good quality. This goal is in accordance with the aspirations of the state as stated in Article 3 of Law No. 20 of 2003 concerning the National Education System. The importance of the role of professional social workers in the school environment must also be considered. This research aims to find out how the approaches and theories used in the context of education. The literature method is used as an approach in this research, by collecting information or academic works that focus on library ownership or studies that focus on critical and in-depth examination of library resources to address existing problems. As a nation, we do not want to be just an object of influence of other countries, therefore education in Indonesia must be able to participate positively in the current era of globalization. For this reason, we must immediately prepare to face the challenges of this era, one of which is by preparing human resources through the education process.